Handbook of Florida Fence and Property Law: Eminent Domain - Michael T. Olexa; Joshua A. Cossey (EDIS, 2007)
Revised! Circular 1242, by Michael T. Olexa and Joshua A. Cossey, provides a basic overview of many rights and responsibilities that farmers and landowners have under Florida's fencing and property law. Published by the UF Department of Food and Resource Economics, December 2006.